Trunk-Rotation Differences at Maximal Reach of the Star Excursion Balance Test in Participants With Chronic Ankle Instability - de la Motte, Sarah (J Athl Train, 2015)
CONTEXT: Functional reach on the Star Excursion Balance Test is decreased in participants with chronic ankle instability (CAI). However, comprehensive 3-dimensional kinematics associated with these deficits have not been reported. OBJECTIVE: To determine if lower extremity kinematics differed in CAI participants during anteromedial, medial, and posteromedial reach on the Star Excursion Balance Test. DESIGN: Case-control study. SETTING: Sports medicine research laboratory. PATIENTS OR OTHER PARTICIPANTS: Twenty CAI participants (age = 24.15 ± 3.84 years, height = 168.95 ± 11.57 cm, mass = 68.95 ± 16.29 kg) and 20 uninjured participants (age = 25.65 ± 5.58 years, height = 170.14 ± 8.75 cm, mass = 69.89 ± 10.51 kg) with no history of ankle sprain. We operationally defined CAI as repeated episodes of ankle “giving way” or “rolling over” or both, regardless of neuromuscular deficits or pathologic laxity. All CAI participants scored ≤26 on the Cumberland Ankle Instability Tool. INTERVENTION(S): Star Excursion Balance Test reaches in the anteromedial, medial, and posteromedial directions. The CAI participants used the unstable side as the stance leg. Control participants were sex, height, mass, and side matched to the CAI group. The 3-dimensional kinematics were assessed with a motion-capture system. MAIN OUTCOME MEASURE(S): Group differences on normalized reach distance, trunk, pelvis, and hip-, knee-, and ankle-joint angles at maximum Star Excursion Balance Test reach. RESULTS: No reach-distance differences were detected between CAI and uninjured participants in any of the 3 reach directions. With anteromedial reach, trunk rotation (t(1,38) = 3.06, P = .004), pelvic rotation (t(1,38) = 3.17, P = .003), and hip flexion (t(1,38) = 2.40, P = .002) were greater in CAI participants. With medial reach, trunk flexion (t(1,38) = 6.39, P = .05) was greater than for uninjured participants. No differences were seen with posteromedial reach. CONCLUSIONS: We did not detect reach-distance differences in any direction. However, participants with CAI rotated the trunk and pelvis more toward the stance leg than did stable-ankle participants during anteromedial and medial reach, possibly to help maintain a proximal stable posture and compensate for distal instability. These joint-angle differences with Star Excursion Balance Test performance may represent unique compensatory patterns for those with CAI.